(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Worldwide, breast cancer is the most frequently diagnosed life-threatening cancer and the leading cause of cancer death among women. Approximately 7% of all breast cancers are diagnosed in women <40 years of age. Young age at diagnosis influences prognosis negatively as they present with more advanced disease at diagnosis and a poorer 5-year survival than older patients. The present study includes breast cancer patients in the age group of 18 to 40 years to enrich our knowledge about clinical presentation and pathological characteristics of breast cancer. To find out the clinical presentation and pathological characteristics of breast cancer among the young age group. This cross-sectional study was done over 100 cases of histopathologically proven breast cancer from structured Questionnaire was used as data collection tool. Mean age was 33.89 years. Among the respondents 88% are married. Among the total studied population 61 respondents had the history of oral contraceptive pill use. Family history of cancer presents in 13.0% respondents and absent in 87.0% respondents. Among the respondents 95% patients presented with lump in the breast. 97.0% had invasive carcinoma 90% were invasive ductal carcinoma in which 46.0% were moderately differentiated. 51.0% patients were in the stage IIa and stage IIb.